EFEKTIVITAS MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR SISWA PADA PELAJARAN EKONOMI - Heribertus Kurniawan Apriliyanto; Yohanes Harsoyo (Jurnal Pendidikan Ekonomi dan Akuntansi, 2023)
This study aims to determine and analyze the effectiveness of the process oriented guided inquiry learning model to improve students' critical thinking skills and independent learning in economics subjects at SMA Pangudi Luhur Sedayu.This research is a classroom action research (CAR) with one action cycle conducted at SMA Pangudi Luhur Santo Louis IX Sedayu. The research subjects were 25 students of class XI IPA 1, while the objects of the study were the ability to think critically and study independently in economics. Data collection techniques using tests and questionnaires.The results of the data analysis show that: 1) the level of students' critical thinking skills before the application of the process oriented guided inquiry learning model is still quite critical; 2) the level of student learning independence before the application of the process oriented guided inquiry learning model was classified as less independent; 3) the application of the process-oriented guided inquiry learning model can improve students' critical thinking skills through a number of learning activities that condition students to carry out discussion activities in groups to encourage students to find new ideas and ideas, solve problems in a variety of ways; and 4) Application of the process-oriented guided inquiry learning model can increase student learning independence, where through flexible, collaborative and creative learning activities that allow students to study material independently, work on questions independently, and carry out discussions and communication among students with teachers more actively and flexibly.Keywords: critical thinking skills, independent learning, process oriented guided inquiry learning, classroom action research